Macrophage-Regulatory T Cell Interactions Promote Type 2 Immune Homeostasis Through Resistin-Like Molecule α - Li, Jiang; Kim, Sang Yong; Lainez, Nancy M.; Coss, Djurdjica; Nair, Meera G. (Frontiers in Immunology, 2021)
RELMα is a small, secreted protein expressed by T helper type 2 (Th2) cytokine activated “M2” macrophages in helminth infection and allergy. At steady state and in response to Th2 cytokines, RELMα is highly expressed by peritoneal macrophages, however, its function in the serosal cavity is unclear. In this study, we generated RELMα TdTomato reporter/knockout (RαTd) mice and investigated RELMα function in IL-4 complex (IL-4c)-induced peritoneal inflammation. We first validated the RELMαTd/Td transgenic mice and showed that IL-4c injection led to the significant expansion of large peritoneal macrophages that expressed Td but not RELMα protein, while RELMα+/+ mice expressed RELMα and not Td. Functionally, RELMαTd/Td mice had increased IL-4 induced peritoneal macrophage responses and splenomegaly compared to RELMα+/+ mice. Gene expression analysis indicated that RELMαTd/Td peritoneal macrophages were more proliferative and activated than RELMα+/+ macrophages, with increased genes associated with T cell response, growth factor and cytokine signaling, but decreased genes associated with differentiation and maintenance of myeloid cells. We tested the hypothesis that RαTd/Td macrophages drive aberrant T cell activation using peritoneal macrophage and T cell co-culture. There were no differences in CD4+ T cell effector responses when co-cultured with RELMα+/+ or RELMαTd/Td macrophages, however, RELMαTd/Td macrophages were impaired in their ability to sustain proliferation of FoxP3+ regulatory T cells (Treg). Supportive of the in vitro results, immunofluorescent staining of the spleens revealed significantly decreased FoxP3+ cells in the RELMαTd/Td spleens compared to RELMα+/+ spleens. Taken together, these studies identify a new RELMα regulatory pathway whereby RELMα-expressing macrophages directly sustain Treg proliferation to limit Th2 inflammatory responses.